Metagenomic Bioprospecting for Lignocellulosic Enzymes from Bacterial Communities of Humus Obtained from Natural and Man-Made Forests in Tomohon, North Sulawesi, Indonesia - Mantiri, Feky Recky; Kairupan, Carla Felly; Sudewi, Sri; Mantiri, Vic Axel Daniel (Journal of Applied Agricultural Science and Technology, 2025)
Lignocellulosic biomass degradation is crucial for various industrial applications. Traditional enzyme discovery methods, limited by culturing constraints, fail to capture the vast enzymatic potential of uncultured microorganisms. Metagenomic bioprospecting provides a culture-independent avenue to explore this untapped genetic diversity. This research characterizes the microbial communities and their functional capabilities in a natural forest (Mahawu Mountain Forest, MMF) and a man-made forest (Tomohon City Forest, TCF) located in North Sulawesi, Indonesia, aiming to assess the influence of forest type on microbial ecological dynamics and lignocellulose degradation mechanisms. Comparative soil analysis revealed MMF had slightly alkaline pH (7.1), cooler temperature (21°C), and dark grayish-brown Andosol, while TCF exhibited a neutral pH (6.9), warmer temperature (23°C), and brown Andosol. High-throughput 16S rRNA sequencing demonstrated that TCF harbors greater bacterial richness (125 vs. 91 observed OTUs) and diversity (Shannon index 4.44 vs. 4.11), likely influenced by anthropogenic activities. Taxonomic profiling showed that Proteobacteria dominate both sites (MMF: 42.37%; TCF: 56.08%), with Actinobacteria significantly more abundant in MMF (34.08% vs. 5.84%). Functional prediction via PICRUSt analysis highlighted TCF’s enrichment in stress-responsive genes and ABC transporters, whereas MMF exhibited elevated lipid metabolism and specialized lignin-degradation pathways (e.g., 3-hydroxyphenylacetate degradation). These findings suggest that TCF's heterogeneous environment supports microbial versatility, while MMF's stable conditions promote specialization in decomposition. Both forests represent promising reservoirs for lignocellulolytic enzyme discovery, with implications for sustainable biotechnological applications. This study underscores the importance of forest management in shaping soil microbial communities and highlights the value of preserving natural ecosystems for future bioresource exploration.